High-Risk Cardiovascular Patients: Clinical Features, Comorbidities, and Interconnecting Mechanisms - Schuett, Katharina Andrea; Lehrke, Michael; Marx, Nikolaus; Burgmaier, Mathias (Frontiers in Immunology, 2015)
Cardiovascular disease is the leading cause of death in the Western world with an increase over the last few decades. Atherosclerosis with its different manifestations in the coronary artery tree, the cerebral as well as peripheral arteries is the basis for cardiovascular events such as myocardial infarction, stroke or cardiovascular death. The pathophysiological understanding of the mechanisms that promote the development of vascular disease has changed over the last few decades, leading to the recognition that inflammation and inflammatory processes in the vessel wall are major contributors in atherogenesis. In addition, a subclinical inflammatory status e.g. in patients with diabetes or the presence of a chronic inflammatory disease such as rheumatoid arthritis have been recognized as strong risk factors for cardiovascular disease. The present review will summarize the different inflammatory processes in the vessel wall leading to atherosclerosis and highlight the role of inflammation in diabetes and chronic inflammatory diseases for cardiovascular morbidity and mortality.